Water-energy-food nexus: Issues and alternatives - Chand, Prem; Rao, Sulakshana; Pal, Suresh (Indian Farming, 2020)
In India, water scarcity is undoubtedly a long-standing issue considering its use for agriculture as well as for basic needs. Agricultural sector is responsible for 78% of water use in the country and demand for the sector will increase further with increasing population and transformation of diets. This article highlights issues is water-energy-food nexus and suggest technological and policy options for sustainable use of water. The high water foot prints of rice and wheat in traditional belts streamlines the much needed water availability based cropping pattern realignment across the zones. Technology assisted cultivation in the form of seed varieties or method of sowing or improved cultivation practices is advocated for long term sustainability. The higher irrigation efficiency sprinkler and drip irrigation systems and conservation agriculture, not only helps in reducing water footprints but also have potential to mitigate GHG emission. Management of postharvest food wastage will also play significant role in reducing environmental footprints.